Association between Body Mass Index and Prognosis of Colorectal Cancer: A Meta-Analysis of Prospective Cohort Studies - Lee, Junga; Meyerhardt, Jeffrey A.; Giovannucci, Edward; Jeon, Justin Y. (PLOS ONE, 2015)
Studies have reported conflicting results on the association between body mass index (BMI) and prognosis of colorectal cancer. Therefore, we have conducted a meta-analysis of prospective studies, which examined the association of pre- and post-diagnostic BMI with colorectal cancer-specific mortality and all-cause mortality in patients with colorectal cancer. We searched Medline and EMBASE database published between 1970 and September 2014. A total of 508 articles were identified, of which 16 prospective cohort studies were included for the current meta-analysis. The analysis included 58,917 patients who were followed up over a period ranging from 4.9 to 20 years (median: 9.9 years). We found that being underweight before cancer diagnosis was associated with increased all-cause mortality (Relative risk [RR]: 1.63, 95% CI: 1.18–2.23, p < 0.01) and being obese (BMI ≥ 30 kg/m2) before cancer diagnosis was associated with increased colorectal cancer-specific mortality (RR: 1.22, 95% CI: 1.003–1.35, p < 0.01) and all-cause mortality (RR: 1.25, 95% CI: 1.14–1.36, p < 0.01). On the other hand, being underweight (RR: 1.33, 95% CI: 1.20–1.47, p < 0.01), obese (RR: 1.08, 95% CI: 1.03–1.3, p < 0.01), and class II/III obese (BMI ≥ 35 kg/m2; RR: 1.13, 95% CI: 1.04–1.23, p < 0.01) after diagnosis were associated with significantly increased all-cause mortality. Being obese prior to diagnosis of colorectal cancer was associated with increased colorectal cancer-specific mortality and all-cause mortality, whereas being obese after diagnosis was associated with increased all-cause mortality. The associations with being underweight may reflect reverse causation. Maintaining a healthy body weight should be discussed with colorectal cancer survivors.